Role of the tissue-type plasminogen activator -7351C > T and plasminogen activator inhibitor 1 4G/5G gene polymorphisms in central serous chorioretinopathy. (2nd November 2018) - Malle, Eva Maria; Posch-Pertl, Laura; Renner, Wilfried; Pinter-Hausberger, Silke; Singer, Christoph; Haas, Anton; Wedrich, Andreas; Weger, Martin
ABSTRACT: Background : Central serous chorioretinopathy (CSC) is a common chorioretinal disease, characterized by choroidal hyperpermeability leading to neurosensory and/or retinal pigment epithelial detachments. Hypofibrinolysis due to higher plasma concentrations of plasminogen activator type 1 (PAI-1) or lower activity of tissue-type plasminogen activator (t-PA) has been implicated in the pathogenesis of CSC. Functional polymorphisms in the PAI-1 ( SERPINE1 ) and t-Pa ( PLAT ) are thus potential risk factors for CSC. The aim of the present study was therefore to investigate a hypothesized association between the PAI-1 4G/5G and the t-PA -7351C > T gene variants and the presence of CSC. Methods : The present study comprised 172 CSC patients and 313 control subjects. Genotypes of the PAI-1 4G/5G and the t-PA -7351C > T polymorphisms were determined by TaqMan TM fluorogenic 5′-exonuclease assays. Results : Allelic frequencies or genotype distributions of neither the PAI-1 4G/5G nor the t-PA -7531C > T polymorphisms were significantly different between patients with CSC and control subjects (PAI-1 4G/4G: 24.4% vs. 20.4, p = 0.36; t-PA -7351CC: 42.4% vs. 46.0%, p = 0.50). After adjusting for age and gender presence of the PAI-1 4G/4G genotype was associated with a non-significant odds ratio (OR) of 1.21 (95% confidence interval [95% CI]: 0.77–1.92, p = 0.41), while homozygosity for the t-PA -7351C allele yielded a non-significant OR of 0.91 (95% CI: 0.62–1.33, p = 0.62) for CSC. Conclusion : The present study suggests that both the t-PA -7351C > T and the PAI-1 4G/5G gene variants are unlikely major risk factors for CSC.